2002
DOI: 10.1046/j.1365-294x.2002.01647.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity of arbuscular mycorrhizal fungi and patterns of host association over time and space in a tropical forest

Abstract: We have used molecular techniques to investigate the diversity and distribution of the arbuscular mycorrhizal (AM) fungi colonizing tree seedling roots in the tropical forest on Barro Colorado Island (BCI), Republic of Panama. In the first year, we sampled newly emergent seedlings of the understory treelet Faramea occidentalis and the canopy emergent Tetragastris panamensis , from mixed seedling carpets at each of two sites. The following year we sampled surviving seedlings from these cohorts. The roots of 48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
291
4
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(328 citation statements)
references
References 56 publications
25
291
4
8
Order By: Relevance
“…Further information is now required on mycorrhizal respiration in different tropical forests where nutrient limitation of plant growth and community composition of mycorrhiza may vary (e.g. Husband et al, 2002cf. Lovelock et al, 2003, and on how increased concentrations of atmospheric CO 2 will affect the allocation of C from plants to mycorrhizal fungi in tropical forests.…”
Section: Resultsmentioning
confidence: 99%
“…Further information is now required on mycorrhizal respiration in different tropical forests where nutrient limitation of plant growth and community composition of mycorrhiza may vary (e.g. Husband et al, 2002cf. Lovelock et al, 2003, and on how increased concentrations of atmospheric CO 2 will affect the allocation of C from plants to mycorrhizal fungi in tropical forests.…”
Section: Resultsmentioning
confidence: 99%
“…Studies to date have focused on quantifying potential responses in fungal abundance measures, primarily root colonization and spore numbers (see Table 1). However, mycorrhizal fungi occur as species assemblages in ecosystems and in roots of individual plants (Johnson et al 1992;Husband et al 2002;Vandenkoornhuyse et al 2003;Mummey et al 2005). The species composition of a mycorrhizal fungal assemblage can be important to mycorrhizal functioning (e.g., van der Heijden et al 1998).…”
Section: Conclusion and Research Recommendationsmentioning
confidence: 99%
“…However, some studies showed that highly diverse plant communities may not supported a higher AMF diversity compared with depauperate plant communities (Johnson et al, 2003a;Börstler et al, 2006), suggesting that factors other than plant diversity are also important in determining AMF communities. Distinctions between AMF communities may be partially caused by ecological specificity among fungale plant pairs (Helgason et al, 1998;Vandenkoornhuyse et al, 2003) or effects of season and host plant development stage (Husband et al, 2002a), and also possibly a result of environmental disturbance. For example, farming practices may play a key role in determining the AMF communities at both the local and regional scales (van der Gast et al, 2011).…”
Section: Introductionmentioning
confidence: 99%